Teleradiology Usage and User Satisfaction with the Telemedicine System Operated by Médecins Sans Frontières - Halton, Jarred; Kosack, Cara; Spijker, Saskia; Joekes, Elizabeth; Andronikou, Savvas; Chetcuti, Karen; Brant, William E.; Bonnardot, Laurent; Wootton, Richard (Frontiers in Public Health, 2014)
Médecins Sans Frontières (MSF) began a pilot trial of store-and-forward telemedicine in 2010, initially operating separate networks in English, French and Spanish; these were merged into a single, multilingual platform in 2013. We reviewed the pattern of teleradiology usage on the MSF telemedicine platform in the four-year period from April 2010. In total, 564 teleradiology cases were submitted from 22 different countries. A total of 1114 files were uploaded with the 564 cases, the majority being of type JPEG (n=1081, 97%). The median file size was 938 kB (interquartile range, IQR 163 to 1659). A panel of 14 radiologists was available to report cases, but most (90%) were reported by only four radiologists. The median radiologist response time was 6.1 hours (IQR 3.0 to 20). A user satisfaction survey was sent to 29 users in the last six months of the study. There was a 28% response rate. Most respondents found the radiologist's advice helpful and all of them stated that the advice assisted in clarification of a diagnosis. Although some MSF sites made substantial use of the system for teleradiology, there is considerable potential for expansion. More promotion of telemedicine may be needed at different levels of the organisation to increase engagement of staff.